2016
DOI: 10.1177/1049909116680990
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hypothetical Death Scenarios on Multidimensional End-of-Life Care Preferences

Abstract: Our hypothesis that multidimensional EOL care preferences would differ based on hypothetical death scenarios was partially supported and suggests the need for disease-specific EOL care discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Thus, Advanced Dementia was perceived to be associated with a lower quality of life than Physical Disability, which is consistent with the literature that reports that mental disabilities, such as depression, are perceived as having a higher negative impact on daily functioning than physical disabilities [49]. This is also consistent with findings by Dassel, Utz [29], in which participants' preference to remain alive and at home was lower in case of Alzheimer's disease than in the case of severe physical disability, and by Clarke, Fistein [28] in which participants' preference to bring life to a peaceful conclusion increased as dementia advanced.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, Advanced Dementia was perceived to be associated with a lower quality of life than Physical Disability, which is consistent with the literature that reports that mental disabilities, such as depression, are perceived as having a higher negative impact on daily functioning than physical disabilities [49]. This is also consistent with findings by Dassel, Utz [29], in which participants' preference to remain alive and at home was lower in case of Alzheimer's disease than in the case of severe physical disability, and by Clarke, Fistein [28] in which participants' preference to bring life to a peaceful conclusion increased as dementia advanced.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to the other factors, religion was the least frequently cited factor affecting preferences for EoL care, but our sample consisted mostly of secular individuals. In contrast, multiple studies reported that religiosity affected EoL preferences, albeit in other populations [29,[60][61][62]. Since participants who identified as religious differed from those who identified as secular, a separate study with a larger representation of religious participants is required for understanding the effect of religion on EoL care preferences.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As given in Table 2, the individual items of the EOL planning tool were recoded and transformed into six scales representing the three EOL value constructs and the three EOL preference constructs identified by exploratory factor analysis done in previous research (Dassel et al, 2018) and confirmed as important by participants in Phase 1. To compute each scale, individual items were summed, divided by the total number of questions answered, then multiplied by the total number of questions.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In our earlier work (Dassel, Utz, Supiano, McGee, & Latimer, 2018), we used a sample of healthy older adults to examine EOL care preferences including preference for life-prolonging measures, willingness to engage in conversations about the timing of ones’ death, and preferences for location of death using three unique hypothetical death scenarios (pancreatic cancer, congestive heart failure, and Alzheimer’s disease). We found significant differences in the patients’ care preferences across these three diseases, most notably in their preferences related to location of death and use of life-sustaining treatment.…”
Section: Background and Objectivesmentioning
confidence: 99%